Caracterización del banco de semillas de arvenses en plantaciones forestales de Gmelina arborea Roxb (melina) en la zona central del litoral Ecuatoriano. - Oñate Espinoza, Johanna Melissa (2020)
This research project was carried out with the objective of analyzing the seed bank of weeds in the different plantations of Gmelina arborea Roxb (melina) of different ages located in the cantons of Valencia, Buena Fe and Quevedo, where 4 sampling units were established at all seven sites. The samples were deposited in germination trays and taken to a greenhouse to avoid contamination and accelerate their germination process. Once the seedlings were suitable for identification, a count was made by species. Using the data obtained, the density and composition of the seed bank, the importance value index, the diversity and similarity between sampled sites were determined. A total of 9719 seeds were identified, 81 species belonging to 36 families and 78 genera, the total density of seeds estimated ranged between 0.13 and 190,60 million seeds / ha. The composition of the seed bank was mainly dicotyledonous herbs, of annual native origin that are mostly dispersed hydrochorically. The species that registered the highest index of importance value were Acalypha alopecuroides, Laportea aestuans, Pilea hialina, Rottboellia cochinchinensis, and Mecardonia procumbens. In most of the study areas, Shannon's diversity was medium, while Simpson's diversity was high. Through the cluster analysis, two groups were differentiated according to the similarity that exists between both seed banks (Amanda and San Carlos; Toachi 2015 and Toachi 2013). The ANOVA revealed that there are no significant differences with respect to the number of individuals in the seed banks. Keywords: Weeds, Density, sampling units and Composition.